Numerical simulation of a forced circulation solar water heating system - Remlaoui, Ahmed; Nehari, Driss; Kada, Benhanifia; Mohd Nasir, Nor Ain Azeany; Abd-Elmonem, Assmaa; Alhubieshi, Neissrien; ElSeabee, Fayza Abdel Aziz; Hussain, Syed M. (Nature Research, 2024)
This study presents a sophisticated numerical simulation model for a forced circulation solar water heating system (FC-SWHs), specifically designed for the unique climatic conditions of Algeria. The model aims to cater to the hot water needs of single-family houses, with a daily consumption of 246 L. Utilizing a dynamic approach based on TRNSYS modeling, the system’s performance in Ain Temouchent’s climate was scrutinized. The model’s validation was conducted against literature results for the collector outlet temperature. Key findings include a maximum monthly average outlet temperature of 38 °C in September and a peak cumulative useful energy gain of 250 W in August. The auxiliary heating system displayed seasonal energy consumption variations, with the highest rate of 500 kJ/hr in May to maintain the water temperature at 60 °C. The energy input at the storage tank’s inlet and the consistent high-level energy output at the hot water outlet were analyzed, with the former peaking at 500 W in May. The system ensured an average water tank temperature (hot, middle and bottom) and water temperature after the mixer, suitable for consumption, ranging between 55 °C and 57 °C. For applications requiring cooler water, the mixer’s exit temperature was maintained at 47 °C. The study’s key findings reveal that the TRNSYS model predicts equal inlet and outlet flow rates for the tank, a condition that is particularly significant when the system operates with high-temperature water, starting at 55 °C. The flow rate at this temperature is lower, at 7 kg/hr, while the water mass flow rate exiting the mixer is higher, at 10.5 kg/hr. In terms of thermal performance, the system’s solar fraction (SF) and thermal efficiency were evaluated. The results indicate that the lowest average SF of 54% occurs in July, while the highest average SF of over 84% is observed in September. Throughout the other months, the SF consistently stays above 60%. The thermal efficiency of the system varies, ranging from 49 to 73% in January, 43–62% in April, 48–66% in July, and 53–69% in October. The novelty of this research lies in its climate-specific design, which addresses Algeria’s solar heating needs and challenges. Major contributions include a thorough analysis of energy efficiency metrics, seasonal auxiliary heating demands, and optimal system operation for residential applications, supporting Algeria’s goal of sustainable energy independence.